Planificação da atenção à saúde na APS: Contribuições para o cuidado e a saúde do trabalhador - Pereira, Mariana Machado dos Santos (2024)
This research refers to the equivalent of a dissertation, presented in the form of two articles, from the Postgraduate Program in Environmental Health and Workers' Health at the Institute of Geography of the Federal University of Uberlândia. The theme of the study was the perception of workers who take part in Health Care Planning, which consists of a process of permanent education that seeks to structure and consolidate the micro and macro processes in Primary Health Care. This research sought to connoisse the perception of health workers belonging to the nine basic family health units in the Irati-PR region with regard to Health Care Planning and possible contributions to the quality of care and Workers' Health. The approach used was quantitative and qualitative, using two data collection instruments: a sociodemographic questionnaire and a semi-structured script for the focus group. Data was collected online and analyzed using SPSS software version 26 and thematic content analysis. A total of 84 workers from the nine basic family health units in the Irati-PR region took part in the survey. Of the participants, 84% were female, 42% were aged between 35 and 44, 75% were in a stable relationship and 82% declared themselves to be white. We noticed that the PAS promotes effective and permanent training among the members who take part in the PAS mentoring, in which a study is carried out on the main weaknesses of the Basic Health Units; so the PAS is developed with a theoretical basis, but also with a survey of work problems